2016
DOI: 10.1111/pace.12941
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Tachycardia Originating in the Vicinity of the Noncoronary Sinus of Valsalva: Report of a Series Including the First Case of Ablation‐Related Complete Atrioventricular Block

Abstract: Focal AT can be successfully mapped and ablated in the NCSV. Higher than usual RF energy levels are sometimes required. Complete AV block is a possible complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
7
0
2
Order By: Relevance
“…Spector et al conducted a meta‐analysis of the RF ablation outcome of SVTs and reported that the percentage of patients with AVB was 1.7% for AVNRT and 0.8% for APs, and the need for a pacemaker was 0.7% for AVNRT and 0.3% for APs (all AP locations were included). Barkagan et al assessed the outcome of RF ablation in nine patients with an AT originating from the vicinity of the noncoronary sinus of Valsalva and reported that a successful RF ablation of the AT was associated with complete AVB requiring an implantation of a permanent pacemaker in one patient.…”
Section: Discussionsupporting
confidence: 88%
“…Spector et al conducted a meta‐analysis of the RF ablation outcome of SVTs and reported that the percentage of patients with AVB was 1.7% for AVNRT and 0.8% for APs, and the need for a pacemaker was 0.7% for AVNRT and 0.3% for APs (all AP locations were included). Barkagan et al assessed the outcome of RF ablation in nine patients with an AT originating from the vicinity of the noncoronary sinus of Valsalva and reported that a successful RF ablation of the AT was associated with complete AVB requiring an implantation of a permanent pacemaker in one patient.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, the complication of complete atrioventricular block was reported by NCC-A. 15 On the contrary, 48 of the 55 patients with para-Hisian APs in our study were successfully ablated by IVC-A with lower On the basis of the results of the present study, a new catheter ablation strategy for para-Hisian APs can be delineated. If a para-Hisian AP is identified, the degree of fusion between the ventricular and the atrial potentials during retrograde AP conduction should be assessed.…”
Section: Catheter Ablation Strategy For Para-hisian Apsmentioning
confidence: 75%
“…Evaluation of the P wave during periods of AV block (Figure , arrow) reveal a biphasic morphology in lead aVF (negative/positive) incompatible with typical AVNRT and characteristic of AT arising from the noncoronary cusp (NCC) of the aortic valve . In this case, NCC AT (causing earliest atrial activation at the His bundle region) in the presence of dual AV nodal physiology and sustained slow pathway (SP) conduction (causing simultaneous atrioventricular activation) mimics typical AVNRT . Repetitive retrograde concealment from SP into fast pathway (FP) perpetuates sustained SP conduction during ongoing AT.…”
Section: Discussionmentioning
confidence: 87%